Sustainability, road design and the landscape Institute of Civil Engineers with the Landscape Institute half day seminar : Thursday 29 February 1996 at 1:00 pm - Mulroy, T. J. (Thomas Telford, 1996)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Report on a half-day seminar held at Institution of Civil Engineers on 29 February 1996.